Cellulose and Lignin Nano-Scale Consolidants for Waterlogged Archaeological Wood - Antonelli, Federica; Galotta, Giulia; Sidoti, Giancarlo; Zikeli, Florian; Nisi, Rossella; Davidde Petriaggi, Barbara; Romagnoli, Manuela (Frontiers in Chemistry, 2020)
Waterlogged archaeological wood comes from submerged archaeological sites (in lake, sea, river or wetland) or from land waterlogged sites. Even if the wooden object seems to have maintained the original size and shape, the wood is more or less severely decayed because of chemical and biological factors which modify the normal ratio of cellulose and lignin in the cell wall. Drying procedures are necessary for the musealization but potentially cause severe shrinkages and collapses. The conservation practices focus not only on removing water from wood but also on substituting it with materials able to consolidate the degraded wood cell walls like polymers (e.g. PEG), sugars (e.g. lactitol) or resins (e.g. Kauramin). In the present work three different nano-scale consolidants were tested: lignin nanoparticles (LNPs) obtained form beech wood via a non-solvent method involving dialysis; bacterial nanocellulose (BC) obtained from cultures fed with agro-alimentary waste; cellulose nanocrystals (CNC) chemically extracted from native cellulose. Waterlogged archaeological wood samples of different species (oak, elm, stone pine and silver fir) characterized by different levels of degradation were impregnated with the consolidants. The treatments efficiency was evaluated in terms of macroscopic observation of treated samples, anti-shrink efficiency (ASE) and equilibrium moisture content (EMC). The results obtained for the three consolidants showed substantial differences: LNPs and CNCs penetrated only about a millimeter inside the treated wood, while BC formed a compact layer on the surface of the cell walls throughout the thickness of the samples. In spite of successful BC penetration, physical evaluation of treatment efficiency showed that BC nanoparticles did not obtain a satisfying consolidation of the material. Based on the reported results more focused test protocols are optimized for future consolidation experiments.